2022
DOI: 10.1021/acs.jpclett.1c03774
|View full text |Cite
|
Sign up to set email alerts
|

Room-Temperature Dinitrogen and Carbon Dioxide Activation to Form Nitrogen–Carbon Bonds by Quaternary Cluster Anions: Gold-Assisted Enhancement of Reactivity

Abstract: Coupling conversion of CO 2 and N 2 molecules under mild conditions to form useful N−C bond-containing products has attracted significant attention. However, the activation and direct coupling of such very inert molecules are quite challenging. Herein, we determined that this coupling reaction can be realized by AuNbBO − quaternary anions at room temperature. The well-defined AuNbBO − anions can cleave the NN bond in N 2 and two CO bonds in CO 2 to form a novel product NCNBO − . To the best of our knowledge,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 26 publications
1
33
0
Order By: Relevance
“…12−17 Notably, both homo-and heteronuclear metal species can be produced in gas-phase experiments, and the reactions of these transition metal-based species with N 2 have been extensively studied. In the previously reported reactions, only a few metal-containing species, such as Sc 2 , 18 27 and Nb 2 LiNO − , 28 can fully split NN bonds. Moreover, simultaneous activation of N 2 and H 2 to form NH or NH 2 units has been reported only in our previous work on Sc 3 N + /H 2 /N 2 systems.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…12−17 Notably, both homo-and heteronuclear metal species can be produced in gas-phase experiments, and the reactions of these transition metal-based species with N 2 have been extensively studied. In the previously reported reactions, only a few metal-containing species, such as Sc 2 , 18 27 and Nb 2 LiNO − , 28 can fully split NN bonds. Moreover, simultaneous activation of N 2 and H 2 to form NH or NH 2 units has been reported only in our previous work on Sc 3 N + /H 2 /N 2 systems.…”
mentioning
confidence: 91%
“…29 In addition, there have been few reports about the reactivity of quaternary cluster ions toward N 2 . 27,28 Considering that noble metals, such as Ru, are used in the ammonia catalysts 10 and our observation that niobium atoms exhibit excellent reactivity in N 2 activation and transformation reactions, 24,25,27,28 we designed and synthesized the quaternary heteronuclear metal anions AuNbBO − and studied the reactions with N AuNbBO − anion can subsequently activate N 2 and H 2 at room temperature and efficiently transfer two activated N atoms to form one imido (NH) unit and one NBO moiety. Moreover, the other H atom can transfer to the newly formed NH unit, leading to a small number of amido (*NH 2 ) units.…”
mentioning
confidence: 99%
“…The study of reactions between the gas-phase metal-containing species and small molecules under isolated conditions provides an ideal arena for revealing mechanisms of chemical reactions, such as N 2 fixation and reduction, at a strictly molecular level. It is worth noting that in the gas-phase studies of N 2 reduction reactions, NN triple bonds can be cleaved mediated by metal species, such as Sc 2 , Ta 2 + , Ta 2 C 4 – , Ta 4 + , V 3 C 4 – , V 5 N 5 – , Ta 3 N 3 H 0,1 – , NbH 2 – , NbB 3 O 2 – , Sc 3 N + , FeV 2 C 2 – , FeTaC 2 – , and AuNbBO – , and all of these investigations are focused on roles of transition-metal atoms in reactions with N 2 . In contrast, the function of alkali metal, such as lithium, has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…23 In addition, noble metal atoms, such as M Pt + cations ( M = Cu, Ag, Au) 44,45 and Pt + 46 can directly couple CH 4 and NH 3 to form C–N bonds. Our recent studies 24,47 have shown that the NCO − anion was detected as an isolated product via direct coupling of N 2 and CO 2 mediated by monometallic NbH 2 − anions, while the reduction of CO 2 into CO by NbH 2 − was more competitive.…”
Section: Introductionmentioning
confidence: 99%
“…Some homonuclear and heteronuclear systems are able to cleave NRN triple bonds. [22][23][24][25] Recently, activation and conversion of CO 2 mediated by gasphase clusters have attracted much attention, [26][27][28][29][30][31][32][33] and a dominant channel is the reduction of CO 2 into CO. A variety of metal-containing ions, such as V 2 O + , 34 PtO + , 35 ReO À , 36 Mo x W y O z À , 37 and Nb 2 BN 2 À38 have also been reported. Most synthetic value-added products containing C-N bonds are produced by the reactions of N-containing species with CO 2 , for instance MNH 0-2 + ; [39][40][41] or through the reactions of Ccontaining species with N 2 , such as Ta 2 C 4 À , 42 V 3 C 4 À , 43 and FeV 2 C 2 À .…”
Section: Introductionmentioning
confidence: 99%